Strategic Design of Highly Concentrated Electrolyte Solutions for Mg2+/Li+ Dual-Salt Hybrid Batteries - Cho, Jae-Hyun; Kim, Su Jin; Oh, Jinwoo; Ha, Jung Hoon; Kim, Kwang-Bum; Lee, Kwan-Young; Lee, Jae Kyun (American Chemical Society, 2018)
The available capacity of Mg hybrid batteries is closely related to the number of charge carriers within electrolyte solutions. Therefore, in this study, a dual-salt composition capable of supplying high Li+ concentration was prepared. A dual-salt electrolyte consisting of a LiAlCl4 complex (LACC) and LiN(SO2CF3)(2) (LiTFSI) was found to be an excellent candidate, providing 2.2 M Li+ concentration along with anodic stability up to 3 V (vs Mg/Mg2+). However, the LACC moiety of the above composition first had to undergo a two-step modification procedure comprising "Mg powder treatment" and "conditioning process" to properly implement Mg deposition and stripping at the Mg anode. Spontaneous substitutions of oxidation states between the anionic Al3+ complex and metallic Mg induced by these processes resulted in the generation of Mg2+ complex species within the LACC solutions. The modified LACC was compatible even with 2 M of LiTFSI, the concentration with which we achieved 150 mA h g(-1) capacity of a FePO4 cathode at 1.5 mg cm(-2) loading density, when using an electrolyte volume of only 25.5 mu L cm(-2).
Keywords: ALUMINUM-CHLORIDE COMPLEX; MG BATTERIES; PERFORMANCE; SPECIATION; SYSTEMS